Electrical characterization of lead niobium zirconate titanate (PNZT) for electronic application / Nurul Syazwani Baharum - Baharum, Nurul Syazwani (2012)
Lead niobium zirconate titanate (PNZT) is a PZT thin film with Nb doped. This paper proposes an electrical characterization of PNZT for electronic application. The work will involve with the electrical experimentation using PNZT as a sample. An electrical characterization of PNZT is performed to measure the current-voltage (l-V), resistivity and dielectric to examine PNZT as a potential candidate for sensor application. The resistivity and conductivity for PNZT coated with Pt are 132n /2m and 7.58 x 106 Q.mA respectively. The resistivity of PNZT is unavailable due to its high resistivity. The dielectric constant of PNZT is decreased as frequency increased. It proven that PNZT are suitable in low frequency device due to its high resistance. The dielectric loss of PNZT is decreased as frequency increased. This is due to ionic behavior of PNZT. The conductivity increases as the frequency increases. It shows that, PNZT is capable to be used in the higher frequency electronic devices due to higher conductivity. Results of structural behavioral properties show that the surface of PNZT is rougher as compared to the PNZT coated with Pt. A simulation with LT-Spice has shown that the electrical properties of PNZT are suitable for the pyroelectric/piezoelectric sensor by using a PNZT as capacitor model.